Efficacy of antiseptics containing povidone‐iodine, octenidine dihydrochloride and ethacridine lactate against biofilm formed by Pseudomonas aeruginosa and Staphylococcus aureus measured with the novel biofilm‐oriented antiseptics test. Issue 6 (28th February 2013) - Junka, Adam; Bartoszewicz, Marzenna; Smutnicka, Danuta; Secewicz, Anna; Szymczyk, Patrycja
Abstract: Increasing data suggesting that microorganisms in the biofilm form are among the leading agents of persistent infections of chronic wounds require the development of new approaches to treatment. The aim of this article was to compare the efficacy of three commonly used antiseptics using a biofilm‐oriented approach. Biofilm‐oriented antiseptics test (BOAT), the innovative method, allows to estimate, in a quick and reliable manner, the in vitro activity of working solutions of antiseptics in real contact times against bacteria in the biofilm form and to use the results in the selection of an appropriate antiseptic to treat local infections in the clinical practice.